Identification of Beef Freshness Using Smart Labels Based On Anthocyanin Extract of Purple Cabbage (Brassica Oleracea Var. Capitata L.) - Tommy Eka Chandra Firmansyah; Andrew Setiawan Rusdianto; Winda Amilia (LPPM Universitas Duta Bangsa Surakarta, 2021)
Technological developments ensure food quality and food safety when the Covid-19 pandemic in innovation and application develop rapidly. This is related to food safety which prioritizes body health. Beef is a source of animal protein that is needed to complete nutritional needs to maintain body health and immunity. Beef is a food material that is susceptible to damage due to microbiological and chemical activities. In general, people can only assess the quality and freshness of beef by conducting a sensory evaluation, namely the visual, smell, and texture processes. Sensory evaluations tend to be subjective in nature which is accepted by human reason. It is very ineffective to be used as the same parameter by everyone. Moreover, in support of new habit patterns, there must be renewable technology that can help to reduce direct contact between people being marketed. So we need indicators that can answer the freshness of local beef which is more practical and can facilitate all levels of society. The smart label based on purple cabbage anthocyanin can be a product that helps people see the freshness of beef very easily. Several previous studies have stated that anthocyanins in fruits and vegetables can be a natural indicator that can harm the volatile gases present in meat during the storage process. Purple cabbage (Brassica oleracea var. capitata L.) is known to have a very high anthocyanin content. Besides that, the color density produced by purple cabbage makes it possible to support smart labels. In this study, the extraction of purple cabbage anthocyanin by maceration method used two different types of solvents, namely 96% methanol acidified with 1% HCl and 95% ethanol which was acidified with 3% Citric Acid so that the best total content of purple cabbage anthocyanin was 87,324 mg / 100g with a pH of 5.4. Smart labels are made into edible films with a mixture of chitosan, polyvinyl alcohol, and CMC. The parameters of the freshness level of the meat are based on the pH and Total Microbial tests on beef. From these parameters, changes in smart labels are avoided so that it can change changes in the quality of meat in packaging. Fresh beef has a pH ranging from 6.7 - 7.2 then will experience a decrease in pH to 5.4 - 5.5 (ultimate pH of beef) and then beef tends to increase in pH (spoilage process). In this pH range, it can be divided into three types of groups of smart label indicator color change which results in grouping data on meat products, namely fresh, still fresh, and not fresh.